Knowledge, attitude, and perception towards breast cancer and breast self-examination among non-medical private university students - Foo, Jes Mynn (2022)
Breast cancer is the second most common cancer in the world and one of the most important non-communicable diseases in Malaysia. It poses a huge challenge to countries and causes irreversible effect on the individual. BC screening and health care services is still low in utilization and thus could be due to low BC knowledge, perception, and attitude towards Breast Self-Examination. Therefore, the aim of this study was to determine the knowledge, perception and attitude towards breast cancer and breast self-examination and to identify the factors associated with knowledge of breast cancer in non-medical private university students as it is most effective to start from the early ages of individuals. The sampling method used in the study was convenience sampling and the sample size was calculated to be at 405 students. An adapted questionnaire to assess the Breast cancer Knowledge level, Perception and Attitude towards Breast Self-Examination was distributed to all reachable UTAR students through Microsoft Teams, Whatsapp platform, and approached physically in campus. The data collected were then analyzed using Chi-square test and Logistic Regression on the factors assessed which are Age, Sex, Race, Programme of Study, Year of Study, Living area, Family income and Relationship status in IBM SPSS software statistics version 20. The total participants recruited were 405 students and all responses were processed. The students consist of 42.2% male and 57.8% female which have mean age of 20±1.62. Race was the only significant factor [χ2 (1, n=21) = 6.550, p=0.010] detected to be associated with BC knowledge level and a predictor of BC Knowledge level in the logistic regression model χ2(7) = 9.891, P=0.195 with 6.1% variance (Nagelkerke R Square). 93.1% of students were having poor, 6.9% were having medium, and none were having good BC Knowledge level. Social media was the most common source of information (62%) for BC, 45.9% heard of BSE, 48.4% agree that BSE early detection will increase chance of long-term survival, and 47.4% never attended any demonstration of BSE. In conclusion, the overall findings shows that the non-medical Private university students are having poor levels of BC knowledge. The second major findings from the current study are that race is the only significant factor that is found to affect their level of BC knowledge. The perception and attitude of BSE were explored and suggest the need for improvement in the educational programme.